Structural basis for SARS-CoV-2 envelope protein recognition of human cell junction protein PALS1 - Jin Chai; Yuanheng Cai; Changxu Pang; Liguo Wang; Sean McSweeney; John Shanklin; Qun Liu (Nature Communications, 2021)
SARS-CoV-2 viruses are known to hijack human proteins in order to facilitate their own virulence and replication. In this study, Liu and colleagues present structural analysis of how this phenomenon occurs between SARS-CoV-2 viral envelope protein and human PALS1. The findings provide insights in to viral-host recognition.